MANAJEMEN STRATEGI BENCHMARKING FLUKTUASI SUKU BUNGA (ANALISIS SINTESIS DAN ANTITESIS ATAS RENCANA PEMERINTAH MENGGANTI SBI DENGAN TÂ·BILLS) - Budi Manggala (Jurnal Manajemen., 2001)
The government is scheduled in 2001 to issue short-term bonds known as treasurybills (!-Bills), government securities issued by the Central Bank. Government securitiesconstitute an important part of the reserve assets ratio of commercial banks. Thereforemonetary authorities are using Government Securities as liquidity basis of the bankingsystem in controlling the offering of money. T-bills will replace Bank Indonesiapromissory notes (SB!s) as a benchmark of interest rate fluctuations.The question now is why will the benchmarking of interesr rate fluctuations beturned from SB Is into T-Bill?The objective of this article is to describe the several ways of problemidentifications and the feasibility of problem solving. The problem can be analyzed inseveral ways. Firstly, the present yield curve of SB!s is no longer normal in view of thecurrent prolonged crisis. Secondly, the government may now be too busy managingshort-term liquidity, as the governments liquidity is weakening, and the governmenttherefore feels the need for issuing T-Bills. Thirdly, BI itself as a monetary authority isconsidered as having failed in managing the money in circulation with SB! instrument.T-Bills are also expected to serve as a benchmark of bank interest rate,replacing SB! as monerary instrument